Handbook of mathematical functions : with formulas, graphs, and mathematical tables - Abramowitz, Milton, 1915-1958.; Stegun, Irene A. (New York : Dover, 1972)
This book is a compendium of mathematical formulas, tables, and graphs. It contains a table of analytical integrals, differential equations, and numerical series; and includes tables of trigonometric and hyperbolic functions, tables for numerical integration, rules for differentiation and integration, and techniques for point interpolation and function approximation. Additionally, it devotes a entire section to mathematical and physical constants as fractions and powers of Pi, e, and prime numbers; and discusses statistics by presenting combinatorial analysis and probability functions.
Includes bibliographical references and index.
Keywords: Functions; Mathematics -- Tables